Composition for preparing carbon-based heat storage material, carbon-based heat storage material and preparation method of carbon-based heat storage material
By providing a composition for preparing carbon-based heat storage materials and corresponding preparation methods, the problems of high energy consumption and numerous processes for the preparation of carbon-based heat storage materials in the prior art are solved, and the effect of reducing production costs and improving material performance is achieved.
Patent Information
- Application Number
- CN202411666277.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-03-11
AI Technical Summary
The existing carbon-based thermal storage materials preparation processes consume high energy, many processes or repeated processes, resulting in difficult cost reduction and weak product competitiveness.
A composition for preparing carbon-based heat storage materials and a method for preparing the same, including a thermal conductivity agent, heat storage particles, a binder, a surfactant and water, and prepare the materials through mixing, pressing, drying and a single-firing process to reduce thermal energy applications.
The temperature required for mixing and pressing is reduced, and the material preparation can be completed through only one baking, which reduces the use of thermal energy, reduces production costs, and improves the thermal conductivity, density and strength stability of the heat storage material.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The present application relates to the field of heat storage materials, and in particular, to a composition for preparing a carbon-based heat storage material, a carbon-based heat storage material and a preparation method thereof. Background Art
[0002] Sensible heat storage technology is a more mature and large-scale heat storage technology compared to latent heat storage and chemical heat storage technology, and is also the most successful commercial heat storage technology. Carbon-based heat storage materials have attracted more and more attention in recent years because of their higher thermal conductivity than common sensible heat storage materials such as magnesia bricks, concrete, and molten salt.
[0003] The existing preparation process of carbon-based materials has many or repeated steps and involves thermal energy, that is, thermal energy is used multiple times, resulting in high energy consumption, difficulty in reducing costs, and weak product competitiveness. Summary of the invention
[0004] The purpose of the present disclosure is to provide a composition for preparing a carbon-based heat storage material, a carbon-based heat storage material and a preparation method thereof, which can reduce the application of thermal energy and reduce costs.
[0005] In order to achieve the above-mentioned objectives, the first aspect of the present disclosure provides a composition for preparing a carbon-based heat storage material, based on the total weight of the composition, the composition comprises: 20-70 wt % of a thermal conductor, 20-50 wt % of heat storage particles, 10-35 wt % of a binder, 0.01-2 wt % of a surfactant and 1-10 wt % of water.
[0006] Optionally, based on the total weight of the composition, the composition comprises: 25-65 weight % of a thermal conductor, 19.5-45 weight % of heat storage particles, 15-35 weight % of a binder, 0.01-0.35 weight % of a surfactant and 2.8-7.0 weight % of water; preferably, based on the total weight of the composition, the composition comprises: 30-61 weight % of a thermal conductor, 19.5-38 weight % of heat storage particles, 15-25 weight % of a binder, 0.03-0.35 weight % of a surfactant and 2.97-6.65 weight % of water.
[0007] Optionally, based on the total weight of the composition, the total weight of the surfactant and water is 3-7 wt %; preferably, based on the total weight of the surfactant and water, the content of the surfactant is 5.5 wt % or less.
[0008] Optionally, the thermal conductor includes one or more of flake graphite, microcrystalline graphite, expanded graphite and artificial graphite; preferably flake graphite; optionally, the particle size of the thermal conductor is less than 100 mesh, preferably 100-300 mesh; optionally, the carbon content of the thermal conductor is 80-85% by weight; preferably, the heat storage particles are selected from one or more of artificial graphites; the artificial graphite includes graphitized coke and waste graphite electrodes; preferably graphitized coke; optionally, the particle size of the heat storage particles is 1-3 mm; preferably, the binder includes coal direct liquefaction residue; preferably, the total weight of the coal direct liquefaction residue is taken as the basis , the ash content is 10-30% by weight, the C content is 60-95% by weight, the H content is 2-6% by weight, and the N content is 0.5-2% by weight; preferably, the ash content is 10-25% by weight, the C content is 65-92% by weight, the H content is 3-5.5% by weight, and the N content is 0.5-1.5% by weight; optionally, the particle size of the coal direct liquefaction residue is below 150 mesh, preferably 150-300 mesh; preferably, the surfactant includes one or more of Tween 80, Tween 60, Span 80 and Span 60, preferably one or more of Tween 80, Span 80 and Span 60.
[0009] A second aspect of the present disclosure provides a method for preparing a carbon-based heat storage material, comprising the following steps: S1. Mixing the composition according to the first aspect of the present disclosure to obtain a raw material mixture; S2, subjecting the raw material mixture to a pressing process and a drying process to obtain a preform; S3, calcining the preform.
[0010] Optionally, in step S1, the mixing process includes: mixing the thermal conductor and the binder at 20-40°C for 15-30 minutes to obtain a first mixture; mixing the surfactant and water at 20-40°C for 10-30 minutes to obtain a second mixture; mixing the first mixture with the second mixture at 20-40°C for 20-30 minutes to obtain a third mixture; mixing the heat storage particles with the third mixture at 20-40°C for 10-30 minutes to obtain the raw material mixture.
[0011] Optionally, in step S2, the conditions for the profiling treatment include: a molding pressure of 50-250 MPa, preferably 120-150 MPa; a molding temperature of 20-50°C, preferably 20-40°C; a holding time of 0.01-1h, preferably 0.01-0.05h; the conditions for the drying treatment include: a drying temperature of 102-110°C, preferably 105-108°C; a drying time of 2-12h, preferably 4-6h.
[0012] Optionally, in step S3, the conditions for the calcination treatment include: a calcination temperature of 950-1150°C, preferably 980-1050°C; a calcination time of 2-24h, preferably 4-8h; a calcination atmosphere of nitrogen and / or argon; preferably, a heating rate to the calcination temperature of 2-10°C / min, preferably 3-6°C / min.
[0013] A third aspect of the present disclosure provides a carbon-based heat storage material prepared according to the method described in the second aspect of the present disclosure.
[0014] Through the above technical scheme, the present disclosure provides a composition for carbon-based heat storage material, a carbon-based heat storage material and a preparation method thereof. The carbon-based heat storage material is prepared by using the composition provided by the present disclosure, which can reduce the temperature required for mixing and pressing, and the material preparation can be completed through only one roasting process, reducing the application of thermal energy. The mixing equipment, molds and equipment for pressing required by the present disclosure are also simpler than those of temperature-operated equipment, and the mixing and pressing processes do not need to be equipped with corresponding devices for removing volatiles, thereby reducing production costs.
[0015] Other features and advantages of the present disclosure will be described in detail in the following detailed description. DETAILED DESCRIPTION
[0016] The specific embodiments of the present disclosure are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present disclosure, and are not used to limit the present disclosure.
[0017] A first aspect of the present disclosure provides a composition for preparing a carbon-based heat storage material. The composition comprises, based on the total weight of the composition, 22-70 wt % of a thermal conductor, 19-50 wt % of heat storage particles, 10-35 wt % of a binder, 0.01-2 wt % of a surfactant and 1-10 wt % of water.
[0018] The present disclosure provides a composition for carbon-based heat storage materials. The composition provided by the present disclosure can be used to prepare carbon-based heat storage materials, which can reduce the temperature required for mixing and pressing, and the material preparation can be completed through only one roasting process, reducing the application of thermal energy. The mixing equipment, the molds and equipment used for pressing are also simpler than the equipment with temperature operation, and the mixing and pressing processes do not need to be equipped with corresponding volatile removal devices, which reduces production costs. In addition, the heat storage material prepared by the composition provided by the present disclosure has higher thermal conductivity, smaller fluctuations in density and strength, and a more concentrated range and stable and controllable.
[0019] In a preferred embodiment, based on the total weight of the composition, the composition includes: 25-65 wt% of a thermal conductor, 19.5-45 wt% of heat storage particles, 15-35 wt% of a binder, 0.01-0.35 wt% of a surfactant, and 2.8-6.0 wt% of water. The composition formula provided in this embodiment can be used to prepare a heat storage material with better performance.
[0020] In a more preferred embodiment, the composition comprises: 30-61 wt% of a thermal conductor, 19.5-38 wt% of heat storage particles, 15-25 wt% of a binder, 0.03-0.35 wt% of a surfactant, and 2.97-6.65 wt% of water. The composition provided in this embodiment can further improve the formability of the semi-finished heat storage material prepared at room temperature, and improve the thermal conductivity, strength and density of the heat storage material.
[0021] In a preferred embodiment, in the composition, the contents of the surfactant and water have the following relationship: based on the total weight of the composition, the total weight of the surfactant and water is 3-7 wt %. By controlling the contents of the surfactant and water in the composition within the range of this embodiment, the performance of the heat storage material prepared by the composition can be further improved.
[0022] In a preferred embodiment, the content of the surfactant is 5.5 wt % or less based on the total weight of the surfactant and water. By controlling the content relationship between the surfactant and water in the composition, the performance of the heat storage material prepared at room temperature can be further improved and the application of heat energy can be reduced.
[0023] In a specific embodiment, the thermal conductor includes one or more of flake graphite, microcrystalline graphite, expanded graphite and artificial graphite, etc.; preferably flake graphite; optionally, the particle size of the thermal conductor is less than 100 mesh, preferably 100-300 mesh; the carbon content of the thermal conductor is 80-85% by weight; the addition of a thermal conductor to the composition of the present disclosure can improve the thermal conductivity and strength of the obtained heat storage material.
[0024] In one embodiment, the heat storage particles include one or more of artificial graphite, graphitized coke and waste graphite electrodes; preferably graphitized coke; the particle size of the heat storage particles is 1-3 mm; the heat storage particles provided in this embodiment can improve the formability of the composition at room temperature and increase the strength of the obtained heat storage material.
[0025] In one embodiment, the binder includes coal direct liquefaction residue; preferably, based on the total weight of the coal direct liquefaction residue, the ash content is 10-30% by weight, the C content is 60-95% by weight, the H content is 2-6% by weight, and the N content is 0.5-2% by weight; preferably, the ash content is 10-25% by weight, the C content is 65-92% by weight, the H content is 3-5.5% by weight, and the N content is 0.5-1.5% by weight; optionally, the particle size of the coal direct liquefaction residue is less than 150 mesh, preferably 150-300 mesh; the present disclosure uses direct liquefaction residue as a binder, which can increase the uniformity of the mixture and the formability of the mixture, while improving the range stability and controllability of the compressive strength.
[0026] In one embodiment, the surfactant includes one or more of Tween 80, Tween 60, Span 80 and Span 60, preferably one or more of Tween 80, Span 80 and Span 60; optionally, the acid value of Tween 80 and Tween 60 is 0-2mgKOH / g, the hydroxyl value is 65-80mgKOH / g, and the saponification value is 45-55mgKOH / g; the acid value of Span 80 and Span 60 is 5.5-8mgKOH / g, the hydroxyl value is 190-270mgKOH / g, and the saponification value is 135-160mgKOH / g. The surfactant provided in this embodiment is conducive to improving the wettability of various powders and particles, reducing dust, improving the formability of the mixture, reducing the molding defect rate, etc., improving the compactness of the green body, and improving the performance of the final heat storage material.
[0027] The raw materials of the composition used in the present disclosure can be purchased through common commercial channels or prepared by known methods.
[0028] A second aspect of the present disclosure provides a method for preparing a carbon-based heat storage material, comprising the following steps: S1. Mixing the composition according to the first aspect of the present disclosure to obtain a raw material mixture; S2, subjecting the raw material mixture to a pressing process and a drying process to obtain a preform; S3, calcining the preform.
[0029] The present disclosure provides a method for preparing a carbon-based heat storage material, which can effectively reduce the use of thermal energy and lower costs.
[0030] In one embodiment, in step S1, the mixing process includes: mixing a thermal conductor and a binder at 20-40°C for 15-30 minutes to obtain a first mixture; mixing a surfactant with water at 20-40°C for 10-30 minutes to obtain a second mixture; mixing the first mixture with the second mixture at 20-40°C for 20-30 minutes to obtain a third mixture; mixing the heat storage particles with the third mixture at 20-40°C for 10-30 minutes to obtain the raw material mixture. The method provided by the present disclosure can be mixed at room temperature, which reduces the application of heat energy compared to heating the mixture.
[0031] In one embodiment, in step S2, the conditions of the press treatment include: a molding pressure of 50-250 MPa, preferably 120-150 MPa; a molding temperature of 20-50° C., preferably 20-40° C.; a holding time of 0.01-h, preferably 0.01-0.05h; The drying conditions include: a drying temperature of 102-110°C, preferably 105-108°C; a drying time of 2-12h, preferably 4-6h. According to the process conditions in this embodiment, especially the preferred process conditions, a heat storage material with better performance can be prepared on the basis of reducing the use of heat energy.
[0032] In one embodiment, in step S3, the conditions for the calcination treatment include: The calcination temperature is 950-1150°C, preferably 980-1050°C; the calcination time is 2-24h, preferably 4-8h; the calcination atmosphere is nitrogen and / or argon atmosphere. According to the calcination conditions in this embodiment, especially according to the preferred calcination conditions, the prepared heat storage material has better performance, such as uniform structure and stable size, low defect rate, etc.
[0033] In a preferred embodiment, in step S3, the heating rate to the calcination temperature is 2-10°C / min, preferably 3-6°C / min. According to the heating rate in this embodiment, the internal pore structure of the calcined product can be made uniform, and the defect rate can be reduced.
[0034] A third aspect of the present disclosure provides a carbon-based heat storage material prepared according to the method described in the second aspect of the present disclosure.
[0035] In a specific embodiment, the thermal conductivity of the carbon-based heat storage material is 20-200 W / mK, preferably 20-100 W / mK; the density is 1.60-1.80 g / cm 3 , preferably 1.60-1.75g / cm 3 ; The compressive strength is 10-25MPa, preferably 10-20MPa.
[0036] The present disclosure is further described in detail below through examples. The raw materials used in the examples can be obtained through common commercial channels.
[0037] Example 1 In this embodiment, the thermal conductor used is flake graphite with a particle size of 100-300 meshes and a carbon content of 80-85% by weight; the heat storage particles are artificial graphite fragments (graphitized coke) with a particle size of 1-3 mm, and the carbon content of the thermal conductor is 83% by weight; the binder is coal direct liquefaction residue, which is not deashed, with an ash content of 14.60% by weight, C, H, and N of 81.83% by weight, 3.99% by weight, and 0.82% by weight, respectively, and a particle size of less than 150 meshes (within the range of 150-300 meshes); the surfactant is Tween 80, with an acid value of 0.4 mgKOH / g, a hydroxyl value of 69.6 mgKOH / g, a saponification value of 45.3 mgKOH / g, and a pH value (1% by weight aqueous solution) of 6.3. The process for preparing the thermal storage material includes the following steps: (1) Mixing: Weigh the sample according to the percentage of the total weight (1000 g), where thermal conductor: heat storage particles: binder powder: surfactant: water = 38.80 wt %: 36.86 wt %: 21.34 wt %: 0.03 wt %: 2.97 wt %. First, mix the thermal conductor and binder powder in a kneader at 25°C for 30 minutes, add the surfactant into the water and stir for 30 minutes, then add the surfactant solution into the kneader and blend at 25°C for 30 minutes, finally add the heat storage particles into the kneader and blend at 25°C for 15 minutes, and discharge the material for use.
[0038] (2) Pressing: Weigh about 120g of the mixture and press it at a pressure of 130 MPa at 25°C for 60 seconds (0.0167 hours). Then demold it and set it aside for later use.
[0039] (3) Drying: Place the green body in an oven at 105°C and dry for 4 hours. Take it out and place it in a dryer to cool to room temperature before taking it out for use.
[0040] (4) Calcination: The dried sample is placed in a carbonization furnace for calcination. In a nitrogen atmosphere, the temperature is increased to 1000°C at a heating rate of 4°C / min and kept at this temperature for 4 hours. After cooling to room temperature in the furnace, it is taken out for use.
[0041] Embodiment 2-9 According to the preparation process in Example 1, the difference from Example 1 is that according to the composition ratio in Table 1, the rest of the process is the same as Example 1 to prepare a carbon-based heat storage material.
[0042] Example 10 This example refers to the preparation method in Example 7, and the difference from Example 7 is that: The binder (coal direct liquefaction residue) was replaced with coal liquefaction asphalt, with an ash content of 0.11% by weight, a C content of 93.89% by weight, an H content of 2.66% by weight, and an N content of 1.64% by weight; the rest of the process was the same as in Example 7 to prepare a carbon-based heat storage material.
[0043] Embodiment 11 This example refers to the preparation method in Example 7, and the difference from Example 7 is that: The surfactant (Tween 80) was replaced by Tween 60, the acid value was 0.2 mgKOH / g, the hydroxyl value was 81.6 mgKOH / g, the saponification value was 42.1 mgKOH / g, and the rest of the process was the same as in Example 7 to prepare a carbon-based heat storage material.
[0044] Examples 12-13 This example refers to the preparation method in Example 7, and the difference from Example 7 is that: The surfactant (Tween 80) was replaced by Span 80 and Span 60 respectively, and the rest of the process was the same as in Example 7 to prepare a carbon-based heat storage material; The acid value of Span 80 is in the range of 5.5-7.5 mgKOH / g, the hydroxyl value is in the range of 193-209 mgKOH / g, and the saponification value is in the range of 145-160 mgKOH / g.
[0045] The acid value of Span 60 is in the range of 5.5-8 mgKOH / g, the hydroxyl value is in the range of 240-270 mgKOH / g, and the saponification value is in the range of 135-155 mgKOH / g.
[0046] Embodiment 14 This example refers to the preparation method in Example 7, and the difference from Example 7 is that: Step (2) Pressing: Weigh approximately 120 g of the mixture and press it at 25°C under a pressure of 50 MPa for 60 seconds (0.0167 hours), then demould and set aside.
[0047] Step (4) Calcination: The dried sample is placed in a carbonization furnace for calcination. In a nitrogen atmosphere, the temperature is raised to 950°C at a heating rate of 10°C / min and kept at this temperature for 4 hours. After cooling to room temperature in the furnace, the sample is taken out for use. The rest of the process is the same as in Example 7.
[0048] Comparative Examples 1-6 According to the preparation process in Example 1, the difference from Example 1 is that according to the composition ratio in Table 1, the rest of the process is the same as Example 1 to prepare a carbon-based heat storage material.
[0049] Table 1
[0050] Test Case The density, strength and thermal conductivity of the carbon-based heat storage materials prepared in the above embodiments and comparative examples were tested, and the test results are listed in Table 2 below.
[0051] Density is measured according to GB / T 24528-2009 (Determination method of bulk density of carbon materials); The compressive strength is measured according to GB / T 1431-2009 (Test method for compressive strength of carbon materials); Thermal conductivity is tested and calculated according to GB / T 22588-2008 (flash method for measuring thermal diffusivity or thermal conductivity).
[0052] Table 2
[0053] According to the data in Table 1-2, The composition formula content in Comparative Examples 1-3 is not within the range provided in the present application, and the thermal conductivity of the heat storage material prepared by using the composition provided in Comparative Examples 1-3 is low; under the same preparation conditions, the thermal conductivity of the heat storage material prepared by using the composition provided in Examples 1-13 of the present disclosure is higher, and the density and strength of the heat storage material can also be taken into account; The composition of Comparative Example 4 does not contain a surfactant, and the strength of the heat storage material prepared using the composition of Comparative Example 4 is relatively low; under the same preparation conditions, the heat storage material prepared using the composition provided in Examples 1-13 of the present disclosure has a relatively high thermal conductivity and a relatively high strength; In Comparative Example 5, no binder is added, and the heat storage material prepared using the composition of Comparative Example 5 has low strength, and the thermal conductivity cannot be detected; under the same preparation conditions, the heat storage material prepared using the composition provided in Examples 1-13 of the present disclosure has high thermal conductivity and high strength; The composition formula of Example 9 is not within the optimized range provided by the present disclosure, and the total weight of the surfactant and water and the proportion of the surfactant in the total amount of the surfactant and water are also not within the optimized range provided by the present disclosure. The heat storage material prepared by the composition of Example 9 has low strength and low thermal conductivity. Under the same preparation conditions, the formulas of the compositions in Examples 1-8 and 10-11 are within the optimized range provided by the present disclosure, the total weight of the surfactant and water and the proportion of the surfactant in the total amount of the surfactant and water are also within the optimized range provided by the present disclosure. The heat storage material prepared by using the compositions in Examples 1-8 and 10-11 has higher thermal conductivity and can also take into account the density and strength of the heat storage material. The composition formulas in Examples 1, 3, 5-6 and 8 are within the further preferred range provided in the present disclosure, while the composition formulas in Examples 2, 4 and 7 are not within the further preferred range provided in the present disclosure. Under the same preparation conditions, the thermal conductivity of the heat storage material prepared by using the composition in Examples 1, 3, 5-6 and 8 is higher, and the density and strength of the heat storage material can also be taken into account; Comparing Example 7 with Example 10, it can be seen that the optimized binder (coal direct liquefaction residue) used in Example 7 has a higher density and strength, and a higher thermal conductivity than that of Example 10 using coal liquefaction pitch as a binder. Comparing Example 7 with Example 11, it can be seen that the optimized surfactant type (Tween 80) is used in Example 7, and the heat storage material prepared from the composition in Example 7 has higher density and strength, and higher thermal conductivity.
[0054] By comparing Example 7 with Example 14, it can be seen that the heat storage material in Example 7 is prepared according to the preferred conditions provided in the present disclosure, and the heat storage material obtained in Example 7 has higher density and strength, and higher thermal conductivity.
[0055] The preferred embodiments of the present disclosure are described in detail above; however, the present disclosure is not limited to the specific details in the above embodiments. Within the technical concept of the present disclosure, a variety of simple modifications can be made to the technical solution of the present disclosure, and these simple modifications all fall within the protection scope of the present disclosure.
[0056] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present disclosure will not further describe various possible combinations.
[0057] In addition, various embodiments of the present disclosure may be arbitrarily combined, and as long as they do not violate the concept of the present disclosure, they should also be regarded as the contents disclosed by the present disclosure.
Claims
1. A composition for preparing a carbon-based heat storage material, characterized in that: Based on the total weight of the composition, the composition includes: 22-70 wt % of a thermal conductor, 19-50 wt % of heat storage particles, 10-35 wt % of a binder, 0.01-2 wt % of a surfactant and 1-10 wt % of water.
2. The composition according to claim 1, characterized in that Based on the total weight of the composition, the composition comprises: 25-65 wt % of a thermal conductor, 19.5-45 wt % of heat storage particles, 15-35 wt % of a binder, 0.01-0.35 wt % of a surfactant and 2.8-7.0 wt % of water; Preferably, based on the total weight of the composition, the composition comprises: 30-61 wt % of a thermal conductor, 19.5-38 wt % of heat storage particles, 15-25 wt % of a binder, 0.03-0.35 wt % of a surfactant and 2.97-6.65 wt % of water.
3. The composition according to claim 1, characterized in that Based on the total weight of the composition, the total weight of the surfactant and water is 3-7% by weight; Preferably, based on the total weight of the surfactant and water, the content of the surfactant is 5.5 wt % or less.
4. The composition according to claim 1, characterized in that The thermal conductor includes one or more of flake graphite, microcrystalline graphite, expanded graphite and artificial graphite; preferably flake graphite; Optionally, the particle size of the thermal conductor is less than 100 mesh, preferably 100-300 mesh; Optionally, the carbon content of the thermal conductor is 80-85% by weight; Preferably, the heat storage particles are selected from one or more of artificial graphites; the artificial graphite includes graphitized coke and waste graphite electrodes; preferably graphitized coke; optionally, the particle size of the heat storage particles is 1-3 mm; Preferably, the binder comprises coal direct liquefaction residue; preferably, based on the total weight of the coal direct liquefaction residue, the ash content is 10-30% by weight, the C content is 60-95% by weight, the H content is 2-6% by weight, and the N content is 0.5-2% by weight; preferably, the ash content is 10-25% by weight, the C content is 65-92% by weight, the H content is 3-5.5% by weight, and the N content is 0.5-1.5% by weight; optionally, the particle size of the coal direct liquefaction residue is less than 150 mesh, preferably 150-300 mesh; Preferably, the surfactant comprises one or more of Tween 80, Tween 60, Span 80 and Span 60, preferably one or more of Tween 80, Span 80 and Span 60.
5. A method for preparing a carbon-based heat storage material, characterized in that: The following steps are involved: S1. Mixing the composition according to any one of claims 1 to 4 to obtain a raw material mixture; S2, subjecting the raw material mixture to a pressing process and a drying process to obtain a preform; S3, calcining the preform.
6. The method according to claim 5, characterized in that In step S1, the mixing process includes: Mix the thermal conductor and the binder at 20-40°C for 15-30 minutes to obtain a first mixture; mix the surfactant and water at 20-40°C for 10-30 minutes to obtain a second mixture; mix the first mixture with the second mixture at 20-40°C for 20-30 minutes to obtain a third mixture; mix the heat storage particles with the third mixture at 20-40°C for 10-30 minutes to obtain the raw material mixture.
7. The method according to claim 5, characterized in that In step S2, the conditions of the profiling process include: The molding pressure is 50-250MPa, preferably 120-150MPa; the molding temperature is 20-50°C, preferably 20-40°C; the holding time is 0.01-1h, preferably 0.01-0.05h; The conditions for the drying treatment include: a drying temperature of 102-110° C., preferably 105-108° C.; and a drying time of 2-12 hours, preferably 4-6 hours.
8. The method according to claim 5, characterized in that In step S3, the conditions of the calcination treatment include: The calcination temperature is 950-1150°C, preferably 980-1050°C; the calcination time is 2-24h, preferably 4-8h; the calcination atmosphere is nitrogen and / or argon; Preferably, the heating rate to the calcination temperature is 2-10°C / min, preferably 3-6°C / min.
9. A carbon-based heat storage material prepared according to the method of any one of claims 5 to 8.
10. The carbon-based heat storage material according to claim 9, characterized in that: The thermal conductivity of the carbon-based heat storage material is 20-200 W / mK, preferably 20-100 W / mK; the density is 1.60-1.80 g / cm 3 , preferably 1.60-1.75 g / cm 3 ; The compressive strength is 10-25MPa, preferably 10-20MPa.
Citation Information
Patent Citations
Method for using residue generated by directly liquefying coal
CN102533373A
Novel solar thermal power generation graphite heat storage material preparation method
CN107673759A
Carbon / carbon composite material and preparation method thereof
CN108585859A
Hydrated salt thermal chemical heat storage composite material as well as preparation method and application thereof
CN114539983A
High-thermal-conductivity adhesive composition and application thereof
CN117844451A